Les indices de ségrégation résidentielle : un outil intégré dans un système d’information géographique - Philippe Apparicio (Unité Mixte de Recherche 8504 Géographie-cités, 2000)
Residential segregation indexes seem to be unrecognized or rarely used in France. The author suggests a definition of residential segregation indices based on a five specific dimensions classification (evenness, exposure, concentration, clustering, centralization) and a presentation of a Mapbasic application. This application has been integrated in the MapInfo software and it allows the automatic calculation of about twenty residential segregation indices.